Acupoint catgut embedding for chronic non-specific low back pain: A protocol of randomized controlled trial - Li, Xiaohui; Yin, Xiuju; Feng, Haiyan; Liao, Wangbin; Zhao, Jiayou; Su, Wu; Fan, Zhiyong; Wu, Shan (Frontiers in Neuroscience, 2023)
Abstract Background: Chronic non-specific low back pain (CNLBP) is a major contributor to global disability. Acupoint catgut embedding (ACE) can greatly improve chronic pain, but there are no rigorous randomised controlled trial (RCT) to confirm the efficiency and safety of ACE in treating CNLBP. Hence, this study is to assess the clinical efficacy and safety of ACE in the treatment of CNLBP. Methods: This is a prospective RCT that will examine the efficacy and safety of ACE in treating CNLBP. The study has received ethical approval from the ethics committee. Eligible participants will be randomised into ACE group and sham ACE group at a ratio of 1:1. Participants in both groups will accept treatments once two weeks with a duration of 8 weeks. All participants will be followed up for 6 months after treatments. The outcome measurements in the study will include visual analogue scale (VAS) scores, Oswestry Disability Index (ODI), Roland Morris Disability Questionnaire (RMDQ) and the Short Form 36-Health Survey (SF-36) as well as adverse event. Data analysis will be conducted using the Statistical Analysis System (version 9.4). Discussion: Results of this trial will provide evidence regarding the clinical efficacy and safety of ACE in treating CNLBP. Ethics and dissemination: This RCT were approved by the medical ethics committee of Guangzhou Panyu Hospital of Chinese Medicine (202230). Results will be published in a peer-reviewed academic journal. Trial registration: This trial has been registered at the Chinese Clinical Trial Registry, numbered ChiCTR2200059245.